Assessing the impact of anti-inflammatory interleukin IL-10 and flosteron, a long-acting corticosteroid, on the course of corneal burn process - Iakymenko, S. A.; Dzhygaliuk, O. V.; Gavryliuk, M. V. (Ukrainian Journal of Ophthalmology, 2025)
Background: Ocular burns are the most severe injury to the eye, and their treatment is still a challenge. Purpose: To assess the temporal changes in and grades of major characteristics of the corneal burn process after anterior chamber injection of anti-inflammatory interleukin (IL)-10 versus subconjunctival injection of flosteron, a long-acting corticosteroid. Material and Methods: Eighteen Chinchilla rabbits were divided into 3 groups of six each, and the right eye of all rabbits received an experimental burn. Thereafter, the right eye of rabbits of group 1 received anterior chamber IL-10 injection, the right eye of rabbits of group 2, subconjunctival flosteron injection, and the right eye of rabbits of group 3 (the control group), a drop of Floxal in the conjunctival sac at days 3, 7, 21 and 30. Results: The main characteristics of corneal inflammatory process (corneal opacity (edema), ocular inflammation, corneal erosion, vascularization, and leucoma) changed with time after burn, and were closely associated with each other, but the scores of these characteristics were lower in the rabbits of groups 1 and 2 compared to controls. In addition, the scores were higher in the rabbits that received IL-10 injections compared to those that received subconjunctival flosteron injections. Conclusion: Subconjunctical corticosteroid injections can be reasonably used for inflammation in ocular burns, and are more advantageous than interleukin injections in the anterior chamber in terms of easy use, safety and availability.